Riflessioni epistemologiche su alcuni aspetti del metodo freudiano - Ceschi, Maria Vittoria (Metapsychologica - rivista di psicanalisi freudiana, 2023)
The objective of this work is to provide epistemological assessments of the architecture, the hypotheses and the logical laws which underpin the Freudian method of investigation. As far as the architecture is concerned it will be highlighted how the method is inspired by Systems Theory, in particular putting into temporal logic sequence two Black Boxes which have specific characteristics. With reference to the logical aspect, it will be shown how the method makes use of hypotheses and rare and sophisticated laws which underpin the whole architecture, such as Negation as Failure and the Consequentia Mirabilis. It will conclude by demonstrating how the entire methodological system is by its nature falsifiable and, specifically, transcendental.